2015
DOI: 10.1007/s00404-015-3985-6
|View full text |Cite
|
Sign up to set email alerts
|

CPE overexpression is correlated with pelvic lymph node metastasis and poor prognosis in patients with early-stage cervical cancer

Abstract: High-level CPE expression was associated with a poor prognosis in early-stage cervical cancer. CPE may serve as a biomarker for predicting PLNM and survival in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…CPE may also have different effects on invasion and migration depending on the tumor type. In glioblastoma (GBM) cells, CPE has been identified as a regulator of RPS6 within the mTORc1 signaling pathway to reduce aerobic glycolysis and migration, which negatively affects tumor cell invasion and migration [20]; in contrast, CPE may promote migration and invasion in other tumor types such as cervical cancer and osteosarcoma [17, 21], although the underlying mechanism remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPE may also have different effects on invasion and migration depending on the tumor type. In glioblastoma (GBM) cells, CPE has been identified as a regulator of RPS6 within the mTORc1 signaling pathway to reduce aerobic glycolysis and migration, which negatively affects tumor cell invasion and migration [20]; in contrast, CPE may promote migration and invasion in other tumor types such as cervical cancer and osteosarcoma [17, 21], although the underlying mechanism remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…This CPE-ΔN variant acts in the nucleus to promote mouse embryonic cortical neuronal survival through up-regulation of expression of many genes that promote proliferation, differentiation, axonal guidance and cell migration, as well as programmed cell death, all events that take place during the formation of the nervous system [22]. Similarly, CPE has been found in the nucleus as revealed by immunohistochemical (IHC) staining in some human cancers [21, 23]. Despite previous studies implicating the CPE variant induces proliferation and invasion in various tumor cell lines and to promote growth and metastasis of tumors in orthotopic models of nude mice, and could potentially be a biomarker in predicting metastasis and recurrence of cancer [13, 16, 23], the complete characterization of this CPE variant has not yet been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…CPE has been shown to be involved in tumorigenesis and cancer progression [5,6,7]. Clinical studies have demonstrated that elevated CPE mRNA and protein levels are correlated with poor prognosis in colorectal [8], hepatocellular carcinoma [9], and cervical cancer patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…CD69 is correlated with poor clinical outcomes and is confirmed to be an independent prognosticator for blood system tumors ( Del Poeta et al, 2012 ). CPE is a member of metallocarboxypeptidases family, and the CPE mRNA expression level can predict tumor recurrence in early-stage hepatocellular carcinoma, and predict poor prognosis in early-stage cervical cancer ( Huang et al, 2016b ; Shen et al, 2016 ). ITM2A is a poorly prognostic biomarker through inducing cell cycle arrest for ovarian cancer ( Nguyen et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%